Preparación del docente para la atención de estudiantes con discapacidad intelectual en Bachillerato General Unificado - Castro Figueroa, Christian Jonathan (2021)
Throughout the history of education, attention to young people with special educational needs, especially those with intellectual disabilities, has become a challenge, for this reason the teachers in their management have had the task of looking for adjusted inclusive and integrative methodologies to their educational needs, however, they do not have the tools or knowledge of the alterations that are sought from this condition, affecting the educational quality and autonomy of these students. Due to this problem, an investigation with a mixed approach is carried out, where analytical and deductive methods were used, as well as exploration techniques such as interviews, surveys and observation…………..